Rural art and industry artistic impression of street children - Glover, Reuben Kwame Agbelengor (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Arts in Painting and Sculpture,